Composition and microstructure evolution in semi-solid cast Al-Zn alloys - George, Sarah Louise (Department of Mechanical Engineering, 2021)
Semi-solid metal casting produces a low porosity, globular microstructure, which makes it an attractive competitor to wrought parts. This research explores the suitability of utilising heat treatable, Al-Zn-Mg-Cu alloys for the production of high strength parts for the automotive and aerospace industries, using the semi-solid metal rheocasting process. The process results in segregation, arising from non-equilibrium solidification, thus placing high demands on the post-solidification homogenisation and solution heat treatments, in order to derive optimum strength during subsequent ageing treatments. If the semi-solid metal castings can be age hardened to the same extent as the equivalent wrought competition, then this process could replace the machining of parts from conventional wrought stock. The semi-solid cast microstructure was investigated with the aid of light microscopy, scanning electron microscopy, elemental dispersive x-ray spectroscopy and electron backscatter diffraction, in order to establish the extent of segregation associated with the as-cast condition. Evolution of the as-cast structures of AA7075 and A713 composition alloys was investigated during subsequent heat treatments, with the view to achieving a fully homogenised structure prior to solution treatment and age hardening. In situ SEM heating experiments were performed, in order to document the evolution of the microstructure during homogenisation treatments. The results from the heating experiments and thermal analysis were used to evaluate the possibility of effective homogenisation processes for removal of the as-cast segregation. Owing to its negative effect on the homogenisation process, incipient melting of the solute-rich phases, identified using differential scanning calorimetry, had to be avoided during heat treatments. It was determined during in situ heating experiments that the interaction between the eutectic and the porosity in the semi-solid cast structure during overheating caused the agglomeration of and morphological changes to the isolated porosity, resulting in the formation of large pores within the previously interglobular regions. This could potentially have a negative impact on the structural integrity of a part in service. The evaluation of the as-cast condition provided insight into the mechanisms involved in the formation of the globular microstructure that is characteristic of SSM processing. Evidence showed that the mechanism was one of alternating planar and cellular growth, and that dendritic growth did not occur during the semi-solid metal rheocasting. This was highlighted by the absence of inter-dendritic liquid and the presence of internal crystallographic misorientations in many of the grains in the as-cast condition.